2018
DOI: 10.4103/aer.aer_195_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of upper lip bite test and ratio of height to thyromental distance with other airway assessment tests for predicting difficult endotracheal intubation

Abstract: Background and Aims:Unanticipated difficult intubation or the failed intubation in operating room and in emergency department is an imperative source of anesthesia-related patient's mortality. The aim of this study is to compare the predictive value of upper lip bite test (ULBT) and ratio of height to thyromental distance (RHTMD) with other commonly used preoperative airway assessment tests for predicting difficult intubation in Indian population.Materials and Methods:In this prospective, single-blinded observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…These findings are consistent with the results of Palczynski et al [ 40 ], who found a sensitivity of 60% and a PPV of 19% for SMD. A poor sensitivity and PPV for this test (8.3 and 3.4%, respectively) were observed by Khatiwada et al [ 41 ] and, in a study by Shobha et al [ 42 ], SMD sensitivity was found to be 3.3% and PPV was 6.25%.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…These findings are consistent with the results of Palczynski et al [ 40 ], who found a sensitivity of 60% and a PPV of 19% for SMD. A poor sensitivity and PPV for this test (8.3 and 3.4%, respectively) were observed by Khatiwada et al [ 41 ] and, in a study by Shobha et al [ 42 ], SMD sensitivity was found to be 3.3% and PPV was 6.25%.…”
Section: Discussionmentioning
confidence: 50%
“…Although repeatedly reported to be a good measure of head extension, previous studies have reported that the SMD has limited clinical value and fails to adequately and solely predict difficult intubations [ 33 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These ndings are consistent with the results of Palczynski et al [40], who found a sensitivity of 60% and a PPV of 19% for SMD. A poor sensitivity and PPV for this test (8.3% and 3.4%, respectively) were observed by Khatiwada et al [41] and, in a study by Shobha et al [42], SMD sensitivity was found to be 3.3% and PPV was 6.25%.…”
Section: Discussionmentioning
confidence: 53%
“…Although repeatedly reported to be a good measure of head extension, previous studies have reported that the SMD has limited clinical value and fails to adequately and solely predict di cult intubations [33,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Several tests have been proposed as prognostic factors for difficult laryngoscopy[ 7 8 10 11 14 24 25 ] however none of them seems to perform well alone, and different combinations between them have been proposed to improve accuracy. [ 18 26 27 ] This is also the case of SMD which is a factor that indirectly combines mandibular space, cervical spine mobility, and neck height. [ 10 20 21 ] Whereas retrognathia, limited cervical spine mobility and short neck have all been individually associated with difficult laryngoscopy,[ 13 14 17 ] their absence does not indicate an easy laryngoscopy and several other factors such as the Mallampati score have to be also assessed.…”
Section: Discussionmentioning
confidence: 99%